Studies on Hydrogen-ion-concentration in Tasar Silkworm (Antheraea proylei Jolly) - M.Chinamen2, Ok. Monoromachanu1* and (Journal of Experimental Sciences, 2011)
Silk is a proteinaceousfibresynthesised by the silkworms from a specialized organ known as silkglands which are nothing but the modified labial glands of certain lepidopteran insects. The hydrogen- ion concentration in the larval haemolymph, silkgland and food leaves of Antheraea proylei has been determined by Ã¢â‚¬Å“ Indicator paper techniqueÃ¢â‚¬Â andÃ¢â‚¬Å“ Universal indicator techniqueÃ¢â‚¬Â. The pH of larval haemolymph and silk gland has been found in range 6.0-6.5 each and 5.5-6.2 in the food leaves. The mean values of haemolymph, silkgland and food leaves have been calculated to be 6.3Ã‚Â±0.0596, 6.21Ã‚Â±0.0586 and 5.88Ã‚Â±0.0772 respectively. The multiple correlation co-efficient of silkgland on haemolymphand food has been found to be R2=93.6% and significant at 1% level.